2009
DOI: 10.1159/000243774
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and Behavioral Aspects of Noonan Syndrome

Abstract: The current paper introduces concise neuropsychological assessment as an essential tool for studying the contribution of cognition and behavior in the expression of genetic syndromes, like Noonan syndrome (NS). Cognitive and behavioral findings in NS show intelligence scores across a wide range, with a mildly lowered average level. Language and motor development are often delayed, but no longer dysfunctional in adulthood. Continuing mild problems in selective and sustained attention are noted, as well as subop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 65 publications
1
35
0
Order By: Relevance
“…One study reported a 34 % rate of clinically significant externalizing symptoms in a sample of children with NS (Alfieri et al 2014), but the threshold for significance was not described and scores were not compared to a control sample. In contrast, other studies have not found that aggressive behaviors and other externalizing symptoms are observed more frequently in individuals with NS than in typically developing individuals (Pierpont et al 2015;Wingbermühle et al 2009). …”
Section: Psychopathology/mental Healthmentioning
confidence: 80%
See 3 more Smart Citations
“…One study reported a 34 % rate of clinically significant externalizing symptoms in a sample of children with NS (Alfieri et al 2014), but the threshold for significance was not described and scores were not compared to a control sample. In contrast, other studies have not found that aggressive behaviors and other externalizing symptoms are observed more frequently in individuals with NS than in typically developing individuals (Pierpont et al 2015;Wingbermühle et al 2009). …”
Section: Psychopathology/mental Healthmentioning
confidence: 80%
“…Individuals with NS have been described as having tendencies toward social immaturity, reduced interaction with peers, and diminished insight in social situations (Wingbermühle et al 2009;Sarimski 2000), although many of these characteristics have not been examined in depth. With respect to social cognitive processing, no studies have directly investigated whether children with NS have impairments on behavioral tasks assessing emotion perception, social attribution of meaning, or other aspects of social cognition.…”
Section: Social Functioningmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, studies in individuals with NS, LS and other clinically related condition (i.e., cardiofaciocutaneous syndrome and Costello syndrome) associated with different mutations in genes of the RAS-MAPK cascade indicated that the heterogeneity in cognitive abilities observed in these patients was at least partially attributable to the individual affected genes and type of mutation involved (Cesarini et al 2009;Pierpont et al 2009). A further study in NS reported general Intelligence Quotient (IQ) and language scores in the low average range with mildly delayed motor and global development (Wingbermuehle et al 2009). Our studies also reported that visual and visuoperceptual abilities are commonly impaired in NS and LS (Alfieri et al 2008).…”
Section: Introductionmentioning
confidence: 99%